2016
DOI: 10.1002/adma.201600054
|View full text |Cite|
|
Sign up to set email alerts
|

Design and Synthesis of FeOOH/CeO2 Heterolayered Nanotube Electrocatalysts for the Oxygen Evolution Reaction

Abstract: FeOOH/CeO2 heterolayered nanotubes supported on Ni foam as efficient oxygen evolution electrocatalysts are reported. The hybrid structure can obviously promote the catalytic performance for the oxygen evolution reaction, such as low onset potential, high electroactivity, and excellent long-term durability. This study provides a new route to the design and fabrication of electrocatalysts with high electroactivity and durability for oxygen evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
333
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 609 publications
(356 citation statements)
references
References 59 publications
(49 reference statements)
16
333
0
Order By: Relevance
“…[11][12][13][14][15] Over the past decades, great progress has been achieved on the development of non-noble metal-based electrocatalysts for both OER and HER. Various nonprecious metal oxides, [9] sulfides, [16] selenides, [17] phosphides, and nitrides [18,19] have been exploited. Among these electrocatalysts, cobalt sulfide (Co 9 S 8 ) is regarded as an attractive electrocatalyst for water splitting due to its high catalytic activity for HER and OER simultaneously, and excellent electrochemical stability.…”
mentioning
confidence: 99%
“…[11][12][13][14][15] Over the past decades, great progress has been achieved on the development of non-noble metal-based electrocatalysts for both OER and HER. Various nonprecious metal oxides, [9] sulfides, [16] selenides, [17] phosphides, and nitrides [18,19] have been exploited. Among these electrocatalysts, cobalt sulfide (Co 9 S 8 ) is regarded as an attractive electrocatalyst for water splitting due to its high catalytic activity for HER and OER simultaneously, and excellent electrochemical stability.…”
mentioning
confidence: 99%
“…38 However, after CeO 2 NPs were deposited on the Ni(OH) 2 nanosheets, the ratio of Ce 3+  : Ce 4+ in the CeO 2 /Ni(OH) 2 hybrid changed compared with pure CeO 2 NPs, indicating that the valence states of Ce in the CeO 2 /Ni(OH) 2 hybrid rearranged. 28 As shown in Fig. 4f, the XPS spectrum of Ni 2p in Ni(OH) 2 /NOSCF showed two major peaks at 853.2 and 870.8 eV corresponding to Ni 2p 3/2 and Ni 2p 1/2 , respectively, which were characteristic of the Ni 2+ state.…”
Section: Resultsmentioning
confidence: 85%
“…Recently, Li et al developed an efficient OER electrocatalyst by supporting FeOOH/CeO 2 on Ni foam and exhibited enhanced OER performance compared with pure FeOOH. 28 They also demonstrated the unique high OSC properties of CeO 2 , such that CeO 2 can straightway absorb the oxygen produced during the OER and accordingly promote the OER. Therefore, the combination of Ni(OH) 2 and CeO 2 to form a CeO 2 /Ni(OH) 2 hybrid will be an efficient route to improve the electrocatalytic performance of Ni(OH) 2 via improving the energy conversion efficiency, and thereby promoting the generation of active species of Ni III/IV for enhancing the OER performance.…”
Section: Introductionmentioning
confidence: 99%
“…[28] TheN yquist plots revealed that the semicircular diameter of Ni-Fe-MOF NSs was smaller than that of XPS was carried out to understand the effect of mixed metals on OER catalysis.C ompared with the Ni-MOF NSs, the peaks of Ni 2p 3/2 and Ni 2p 1/2 in the high-resolution Ni 2p spectrum of the Ni-Fe-MOF NSs shifted to as lightly higher binding energy (a shift of approximately 0.3 eV), indicating amodified local electronic structure of Ni (Figure 3d). [29] Thes tructure-activity relationship (SAR) of these MOF NSs was further studied. The peak shifts and density changes of Ni 2p and Fe 2p indicated strong electronic interactions between the two metals in Ni-Fe-MOF NSs,which could modify the catalytic performance of electrocatalysts.…”
Section: Angewandte Chemiementioning
confidence: 99%